Views of Teaching and Research in Economics and Other Disciplines - Walstad, William B; Allgood, Sam (American Economic Review, 2005)
Anecdotes are often quite suggestive. A graduate student in economics who was serving as a teaching assistant once reported that his major professor came into his office and told him that he was spending too much of his time helping his undergraduate students and not enough time on his research. Was the professor expressing a preference for time spent on teaching over research? Or was the professor suggesting to the student that the academic market rewards research more than teaching? Regardless, the underlying message that gets transferred from such an experience, as early as graduate education and perhaps throughout a career, is that teaching is not as important or valuable as research. Such strong conclusions, however, should not be based on anecdotal evidence. Whether economics professors are less interested in teaching and more interested in research is an empirical question worthy of study. Although teaching and research choices made by economics faculty members reflect both preferences and choice sets, in this study we focus on preferences and use a national survey to compare the teaching and research views of economists with faculty members in other major disciplines.